PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Ni Made Santi Widyasari; Safruddin Safruddin; Awal Nur Kholifatur Rosyidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to determine the effect of cooperative learning model learning type group investigation on mathematics learning outcomes on the cognitive aspects of fifth-grade students at SDN 26 Ampenan. This type of research is an experimental study with a Quasi-Experimental research type Nonequivalent Control Group Design. The population in this study were all fifth-grade students at SDN 26 Ampenan The research sample was taken using a saturated sample technique, where all the population was sampled. Data collection methods used in this study are tests, observations, and documentation. Hypothesis testing in this study uses the formula of independent samples t-test. The results of data analysis using the SPSS Version 16.0 program show the value of t-value is 6.561 and t-table 1.675 where the value of the t-value≥table or by looking at the Sig. (2-tailed) 0,000 ≤ 0.05 at a significance level of 5% with df 51, Ha is accepted, which means there is an influence of cooperative learning model type group investigation on mathematics learning outcomes in the cognitive aspects of fifth-grade students of SDN 26 Ampenan in the 2019/2020 school year. This is evidenced by the syntax of student learning activities using cooperative learning model learning type investigation at the first and second meetings very well implemented.